Nickel and cobalt release from metal alloys of tools - a current analysis in Germany - Kickinger-Lörsch, Anja; Bruckner, Thomas; Mahler, Vera (Contact Dermatitis, 2015)
The former 'EU Nickel Directive' and, since 2009, the REACH Regulation (item 27 of Annex XVII) do not include all metallic objects. The nickel content of tools is not regulated by the REACH Regulation, even if they may come into in prolonged contact with the skin. Tools might be possible sources of nickel and cobalt sensitization, and may contribute to elicitation and maintenance of hand eczema.To perform a current analysis of the frequency of nickel or cobalt release from new handheld tools purchased in Germany.Six hundred unused handheld tools from the German market were investigated with the dimethylglyoxime test for nickel release and with disodium-1-nitroso-2-naphthol-3,6-disulfonate solution for cobalt release.Nickel release was detected in 195 of 600 (32.5%) items, and cobalt in only six (1%) of them. Positive nickel results were nearly twice as frequent in tools 'made in Germany' than in tools without a mark of origin. Tools made in other European countries did not release nickel. Cobalt release was only found in pliers and a saw. A correlation was found between price level and nickel release. Among toolkits, 34.2% were inhomogeneous concerning nickel release.The German market currently provides a large number of handheld tools that release nickel, especially tools 'made in Germany'. For consumer protection, it seems appropriate to include handheld tools in the REACH Regulation on nickel.
EVALuna2:19554